2016
DOI: 10.1002/acn3.330
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of ASL‐MRI and FDG‐PET in the behavioral variant of FTD and AD

Abstract: ObjectiveTo compare the values of arterial spin‐labeled (ASL) MRI and fluorodeoxyglucose (FDG) PET in the diagnosis of behavioral variant of frontotemporal dementia (bvFTD) and Alzheimer's disease (AD).MethodsPartial least squares logistic regression was used to identify voxels with diagnostic value in cerebral blood flow (CBF) and cerebral metabolic rate of glucose (CMRgl) maps from patients with bvFTD (n = 32) and AD (n = 28), who were compared with each other and with cognitively normal controls (CN, n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 57 publications
4
41
0
5
Order By: Relevance
“…Consistent results have been observed between [ 15 O]water PET and ASL (Feng et al, 2004;Ye et al, 2000). Furthermore, joint analyses of [ 18 F]FDG-PET and ASL acquisition have confirmed a good overall correlation between perfusion and glucose uptake in controls (Cha et al, 2013), as well as in patients with AD (Chen, Wolk, et al, 2011), Lewy body dementia (Nedelska et al, 2018), and frontotemporal dementia (Tosun et al, 2016). Recent work has shown relatively strong correlations between ASL imaging and relative perfusion (R1) quantified during dynamic Pittsburgh Compound B (PiB) PET imaging in carriers of autosomal dominant AD mutations (Yan et al, 2018).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Consistent results have been observed between [ 15 O]water PET and ASL (Feng et al, 2004;Ye et al, 2000). Furthermore, joint analyses of [ 18 F]FDG-PET and ASL acquisition have confirmed a good overall correlation between perfusion and glucose uptake in controls (Cha et al, 2013), as well as in patients with AD (Chen, Wolk, et al, 2011), Lewy body dementia (Nedelska et al, 2018), and frontotemporal dementia (Tosun et al, 2016). Recent work has shown relatively strong correlations between ASL imaging and relative perfusion (R1) quantified during dynamic Pittsburgh Compound B (PiB) PET imaging in carriers of autosomal dominant AD mutations (Yan et al, 2018).…”
supporting
confidence: 75%
“…Because of neurovascular coupling, glucose consumption is tightly coupled with CBF (Baron et al, 1982;Furlow, Harrison, & Harrison, 1983), and [ 18 F]FDG-PET and [ 15 O]water PET are highly correlated (Bentourkia et al, 2000;Fox, Raichle, Mintun, & Dence, 1988). Furthermore, joint analyses of [ 18 F]FDG-PET and ASL acquisition have confirmed a good overall correlation between perfusion and glucose uptake in controls (Cha et al, 2013), as well as in patients with AD (Chen, Wolk, et al, 2011), Lewy body dementia (Nedelska et al, 2018), and frontotemporal dementia (Tosun et al, 2016). In ASL imaging, rather than using a radioactive tracer as a label, protons in the blood are labeled with a radiofrequency pulse; the perfusion of these magnetically-tagged protons to each voxel of the brain is then recorded.…”
mentioning
confidence: 98%
“…However, it is still controversially discussed, whether neurons or astrocytes are the main consumers of glucose in the brain (Mergenthaler et al, 2013). In previous studies, it has been shown that during neurodegeneration, the pattern of CBF and metabolic deficits occur in parallel in AD and FTD patients (Verfaillie et al, 2015), and ASL-MRI has similar diagnostic utility as FDG-PET in both AD and FTD (Tosun et al, 2016). In previous studies, it has been shown that during neurodegeneration, the pattern of CBF and metabolic deficits occur in parallel in AD and FTD patients (Verfaillie et al, 2015), and ASL-MRI has similar diagnostic utility as FDG-PET in both AD and FTD (Tosun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence suggests that ASL perfusion imaging may help to distinguish bvFTD from other groups with sensitivity and specificity similar to FDG-PET. 106 For example, sensitivity and specificity for ASL to distinguish bvFTD from AD were 83% and 93%, respectively, compared with 89% and 78% for FDG-PET. Although FDG-PET often can be useful in helping to differentiate bvFTD from AD, frontotemporal hypometabolism can occur in frontal variants of AD as well as in primary psychiatric disorders, both of which can clinically resemble bvFTD.…”
Section: Other Imaging Modalities In Bvftdmentioning
confidence: 97%